2016
DOI: 10.1155/2016/4343084
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Attenuates OGD/R‐Induced Autophagy via Bcl‐2‐Dependent Cross Talk between Apoptosis and Autophagy in PC12 Cells

Abstract: Icariin (ICA), an active component of Epimedium brevicornum Maxim, exerts a variety of neuroprotective effects such as antiapoptosis. However, the mechanisms underlying antiapoptosis of ICA in neurons exposed to oxygen-glucose deprivation and reperfusion (OGD/R) are unclear. The B-cell lymphoma-2 (Bcl-2) protein family plays an important role in the regulation of apoptosis and autophagy through Bcl-2-dependent cross talk. Bcl-2 suppresses apoptosis by binding to Bax and inhibits autophagy by binding to Beclin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Primary hippocampal neurons were subjected to OGD 1.5 h/R 24 h to mimic cerebral I/R injury in vitro as describe in the previous studies (Mo et al, 2016;Feng et al, 2018). In brief, the neurobasal-A culture medium was removed and changed with EBSS (without glucose), subsequently, the cells were put into the hypoxia chamber (STEMCELL) with an atmosphere of 5% CO 2 , 95% N 2 , and 37°C for 1.5 h. After OGD, the medium was transformed into normal culture medium, or different concentrations of ICS II (12.5, 25, 50 mM) or SIL(20 mM) with 5% CO 2 at 37°C for another 24 h. The specific PKG inhibitor Rp-8-Br-cGMP (30 mM) or TrkB inhibitor ANA-12 (10 mM) was added into the corresponding cells 2 h prior to OGD, respectively.…”
Section: Ogd/r Modeling and Treatmentmentioning
confidence: 99%
“…Primary hippocampal neurons were subjected to OGD 1.5 h/R 24 h to mimic cerebral I/R injury in vitro as describe in the previous studies (Mo et al, 2016;Feng et al, 2018). In brief, the neurobasal-A culture medium was removed and changed with EBSS (without glucose), subsequently, the cells were put into the hypoxia chamber (STEMCELL) with an atmosphere of 5% CO 2 , 95% N 2 , and 37°C for 1.5 h. After OGD, the medium was transformed into normal culture medium, or different concentrations of ICS II (12.5, 25, 50 mM) or SIL(20 mM) with 5% CO 2 at 37°C for another 24 h. The specific PKG inhibitor Rp-8-Br-cGMP (30 mM) or TrkB inhibitor ANA-12 (10 mM) was added into the corresponding cells 2 h prior to OGD, respectively.…”
Section: Ogd/r Modeling and Treatmentmentioning
confidence: 99%
“…Normal GP development entails cartilage vascularization and mineralization followed by osteogenesis. However, TD is characterized by tibial metaphyseal cartilage cell proliferation, non-vascular, non-mineralized, and white opaque mass in the GP ( Li et al, 2008 ; Shahzad et al, 2014 ; Nabi et al, 2016a ). TD affected chickens show depression, reduction in physical activities, feeding and drinking, standing difficulty, gait inflexible, movement disorders, and wings support walking ( Jefferies et al, 2000 ; Shahzad et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that, after OGD, the fall in mitochondrial pH provides appropriate conditions for the reduction of nitrite to NO (Butler and Ridd, 2004[ 11 ]). Nitrite-derived NO can prevent neuronal nuclear translocation of NF-κB, an apoptosis-related transcription factor, resulting in the down-regulation of NF-κB target genes that are generally involved in inflammatory response and apoptotic pathways (Miller and Megson, 2007[ 49 ]; Mo et al, 2016[ 50 ]).…”
Section: Discussionmentioning
confidence: 99%